Preparation and Spectroscopic Studies of Cadmium(II), Zinc(II),Mercury(II) and Vanadium(IV) Chelates Azo Ligand Derived from 4-Methyl-7-hydroxycoumarin - Bayader Fathil Abass; Taghreed Mohy Al-Deen Musa; Mahmoud Najim Aljibouri (Indonesian Journal of Chemistry, 2021)
The present paper demonstrates the synthesis and characterization of some transition elements complexes derived from (E)-7-hydroxy-6-((4-methoxyphenyl)diazenyl)-4-methyl-2H-chromen-2-one. The ligand was prepared in the general route of azo dyes by coupling the diazonium salt of 4-methoxyaniline with 4-methyl-7-hydroxycoumarin in sodium hydroxide 10% (w/v) solution. The azo ligand was identified on the basis of elemental analyses, MS, H-NMR and FT-IR spectra. The products of complexes with the new azo dye were isolated by the direct reactions of the metal chlorides of cadmium(II), zinc(II), vanadium(IV) and mercury(II) ions with the alkaline solution of free ligand to afford the colored in the following formulas, complexes[ML2]2H2O formula, M=Cd(II) and Zn(II). However the vanadium(IV) complex was square pyramid in [VOL2]SO42H2O chemical formula. As well as the tetrahedral environment was suggested for mercury(II) complex in formula [HgL2]. The time and mole ratio factors were studied to obtain the optimized conditions of metal complexes formations and the observed data investigated the deprotonation of the azo-dye at pH to range (7–7.5) with 30 min as time of reaction to get pure metal chelates. The TG-DSC study confirmed the thermal stability of complexes at a wide range of average heating in inert gas of analysis and the results observed from loss weight percent investigated the proposed structures of the prepared metal complexes.